The Link between Strategic Cost Management and Value Creation - Mpanza, Sibonelo Sibahle; Aboluwodi, Damilola; Rajaram, Rajendra (The Journal of Accounting and Management, 2025)
The study investigates the link between modern organizational frameworks and stakeholder-oriented strategies to enhance long-term value for various stakeholders. The synthesis of value creation and advanced costing systems reflects the emerging nature of business strategy where value is measured by the broader contribution of the company to society. To achieve the study objective, the research followed a qualitative explanatory approach. Explanatory research clarifies why and explains how there is a relationship between two aspects of the study phenomenon which are, value creation and cost control. A systematic literature review analysis was conducted to emphasize the impact of stakeholder theory and contemporary costing methodologies. The findings reveal that strategic cost management facilitates long-term value creation by aligning cost control, particularly Activity-Based Costing with priorities of the stakeholder. Organizations employing approaches that are stakeholder-centric and modern costing systems and frameworks, an organization can achieve higher returns in the long run, maximize long-term value, and achieve sustainable competitive advantage. To support stakeholder value creation and optimize cost allocation, organizations should integrate traditional costing systems with Activity-Based Costing. To foster sustainable business practices, policymakers can promote frameworks that are stakeholder orientated. By bringing up the stakeholder theory with strategic cost management, the study contributes to the literature on management accounting and offers a framework for value creation in complex business environments.